Influence of exogenous lactoferrin on the oxidant/ antioxidant balance and molecular profile of hormone receptor-positive and -negative human breast cancer cells in vitro - Zalutski, I.V.; Lukianova, N.Y.; Storchai, D.M.; Burlaka, A.P.; Shvets, Y.V.; Borikun, T.V.; Todor, I.M.; Lukashevich, V.S.; Rudnichenko, Y.A.; Chekhun, V.F. (Experimental Oncology, 2017)
Aim: To investigate the mechanisms of cytotoxic activity and pro-/antioxidant effect of lactoferrin on hormone receptor-positive and receptor-negative breast cancer cells in vitro. Materials and Methods: The study was performed on receptor-positive (MCF-7, T47D) and receptor-negative (MDA-MB-231, MDA-MB-468) human breast cancer cell lines. Immunocytochemical staining, flow cytometry, low-temperature electron paramagnetic resonance, and the Comet assay were used. Results: Upon treatment with lactoferrin, the increased levels of reactive oxygen species (ROS) (p < 0.05), NO generation rate by inducible NO-synthase (p < 0.05) and the level of “free” iron (p < 0.05) were observed. Moreover, the effects of lactoferrin were more pronounced in receptor-negative MDA-MB-231 and MDA-MB-468 cells. These changes resulted in increased expression of proapoptotic Bax protein (p < 0.05), reduced expression of the antiapoptotic Bcl-2 protein (p < 0.05) and level of not-oxidized mitochondrial cardiolipin (1.4–1.7-fold, p < 0.05). This, in turn, caused an increase in the percentage of apoptotic cells (by 14–24%, p < 0.05). Cytotoxic effects of lactoferrin were accompanied by an increase in the percentage of DNA in the comet tail and blocking cell cycle at G₂/M phase, especially in receptor-negative cell lines. Conclusion: The study showed that exogenous lactoferrin causes a violation of an antioxidant balance by increasing the level of ROS, “free” iron and NO generation rate, resalting in the blocking of cell cycle at G₂/M-phase and apoptosis of malignant cells.